Implementasi Kebijakan Pengelolaan Dana Kelurahan Dalam Penanganan Dampak Covid-19 Di Kecamatan Matuari Kota Bitung - Sefferson Sumampouw; Shirley Goni; Deysi Tampongangoy (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the implementation of urban village fund management policies in handling the impact of Covid-19 in Matuari District, Bitung City. Research using descriptive qualitative method. With a research focus on communication indicators, resources, disposition and bureaucratic structure with informants taken using a purposive sampling technique consisting of sub-district heads, heads of financial sub-divisions of Matuari District, village heads, heads of LPM sub-districts and the community. Data collection was carried out by means of observation, interviews and documentation. Data analysis using data reduction, data display and data verification. The results showed that the process of conveying information to the community was not directly socialized because there was a prohibition against crowding which relied on community activities, namely when there were ups and downs and did not utilize information technology and delivery was not carried out consistently by village officials. On the resource indicator, the human resources in charge of carrying out the policy are lacking, the required budget must be increased and the facilities need to be increased. The disposition indicator shows that policy implementers already have good attitudes and character but need to be improved in order to gain public trust because discrimination is still found because the provision of assistance is still subjective due to proximity to village officials. The bureaucratic structure indicator shows that the SOP (Standard Operating Procedure) has been clearly stated in Mayor Regulation Number 37 of 2020 and has been implemented properly but not optimally by policy implementers.